Activation of calcium/calmodulin-dependent protein kinase II in obesity mediates suppression of hepatic insulin signaling - Ozcan, Lale; Cristina de Souza, Jane; Harari, Alp Avi; Backs, Johannes; Olson, Eric N.; Tabas, Ira (Cell metabolism, 2013)
A hallmark of obesity is selective suppression of hepatic insulin signaling (“insulin resistance”), but critical gaps remain in our understanding of the molecular mechanisms. We now report a major role for hepatic CaMKII, a calcium-responsive kinase that is activated in obesity. Genetic targeting of hepatic CaMKII, its downstream mediator p38, or the p38 substrate and stabilizer MK2 enhances insulin-induced p-Akt in palmitate-treated hepatocytes and obese mouse liver, leading to metabolic improvement. The mechanism of improvement begins with induction of ATF6 and the ATF6 target p58IPK, a chaperone that suppresses the PERK-p-eIF2α-ATF4 branch of the UPR. The result is a decrease in the ATF4 target TRB3, an inhibitor of insulin-induced p-Akt, leading to enhanced activation of Akt and its downstream metabolic mediators. These findings increase our understanding of the molecular mechanisms linking obesity to selective insulin resistance and suggest new therapeutic targets for type 2 diabetes and metabolic syndrome.
Gesehen am 13.12.2021